A Review of Trends in Distance Education Scholarship at Research Universities in North America, 1998-2007 - Davies, Randall S.; Howell, Scott L.; Petrie, Jo Ann (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
This article explores and summarizes trends in research and scholarship over the last decade (i.e., 1998-2007) for students completing dissertations and theses in the area of distance education. The topics addressed, research designs utilized, and data collection and analysis methods used were compiled and analyzed. Results from this study indicate that most of the distance education research conducted by graduate students in this period of time has been descriptive, often addressing the perceptions, concerns, and satisfaction levels of various stakeholders with a particular distance education experience. Studies of this type typically used self-report surveys and analyzed the data using descriptive statistics. Validating the concern of many distance education scholars, there was a lack of graduate student research aimed at developing a theory base in distance education. On a positive note, projects directly comparing distance education with traditional face-to-face classrooms to determine the merit of specific programs declined significantly in 2007 as compared to 1998. This result might indicate that distance learning is becoming accepted as a viable and important educational experience in its own right. Another encouraging finding was the decreased emphasis on studies focused on technology issues, such as those analyzing the quality of distance education technology and questioning educators’ ability to provide an acceptable technology-enabled distance learning experience.